(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
The early stage of plants is the major determinant of their growth and yield. This study evaluated the germination rate and growth response of Irvingia gabonensis to different Pretreatments and watering regimes. The experiment was laid in a 3×4 factorial experiment in a completely randomized design (CRD) and replicated 15 and 7 times for germination and early growth studies, respectively. Three watering regimes; Watering once; W1=daily (control), W2=watering twice daily, and W3=watering once 2 days with four pre-treatments; P1=No treatment (control), P2= Soaking in water (23oC) for 24 hours, P3= Soaking in warm water (43 oC) for an hour, and P4= Scarification. Seedling height (cm), collar diameter (mm), and Number of leaves were assessed for 12 weeks. The data collected were subjected to analysis of variance and means were separated using Duncan multiple range test at α=0.05. The results showed that P2W2 had the best performance in germination with first emergence on the 13th day and 100% germination on the 28th day. A similar result was recorded for P2W2 in seedling height (24.39±2.068 and 26.82±1.705cm), collar diameter (4.712±0.995 and 4.313±0.922mm), and number of leaves with a mean value of 1.78±0.698. The study concluded that Irvingia gabonensis seeds germinate and seedlings thrive better when soaked in water (23oC) for 24 hours and watered twice daily, hence was recommended for mass seedling production.